Phenotypic and molecular characterization of Ralstonia solanacearum causing bacterial wilt of tomato (Solanum lycopersicum variety cerasiforme) in Selangor - Zakaria, Nurul Salwani (2017)
Cherry tomato (Solanum lycopersicum variety cerasiforme) is a vegetable from Solanaceae family. It is grown and eaten by humans nationwide. However, the results from survey at Fertigation Field show that almost all the cherry tomato plants died caused the outbreak of wilt disease on April, 2017. The disease is caused by Ralstonia solanacearum (R. solanacearum) and occurred in tropical, subtropical and temperate regions of the world. Many commercial tomato cultivars are highly susceptible to bacteria wilt and infections that resulted in wilting of the youngest leaves at the end of branches, yellowing of foliage, stunting and within two to three days, it will death. This study was conducted to isolate and identify R. solanacearum causing tomato bacterial wilt by using phenotypic and molecular characteristics. To achieve the objective, two samples of infected cherry tomato expressing bacterial wilt symptoms were collected from Fertigation Field located in UPM Serdang, Selangor. For phenotypic characterization, the morphology of the bacterial strains isolated from the infected cherry tomato fruits were identified as creamy white, mucoid, virulent, fluidal and irregular. On Kelman’s tetrazolium medium, the colony was large, diffusible brown pigment, elevated and creamy white colonies with pink centre. Gram staining revealed that all strains were Gram-negative with rod shaped, positive for KOH test, catalase test and Kovacs oxidase test. Pathogenicity test revealed that all fruits inoculated with R. solanacearum strains produced bacterial wilt symptoms as observed on naturally infected samples, whereas the control fruits remained asymptomatic. The 16S rDNA polymerase chain reaction (PCR) amplification by using 8F and 1492R primers was performed for molecular identification of four R. solanacearum strains produced amplicon of ~ 1400 basepair (bp). Sequencing analysis showed that all strains were 100% identical to R. solanacearum reference strains in Genbank database (Accession no. AF207891 and U28221). The phylogenetic analysis of 16S rDNA gene sequences clustered all strains into R. solanacearum reference sequences strains.